2015
DOI: 10.1093/jopart/muv002
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Performance-Based Contracting in Human Services: A Quasi-Experiment

Abstract: Performance-based contracting (PBC) is becoming increasingly attractive to public human service agencies. By linking contract compensation to contractors’ performance, PBC is expected to foster quality services, to improve outcomes, and to reduce government monitoring. However, empirical evidence on the effectiveness of PBC remains both limited and mixed. Based on a case study of the Indiana vocational rehabilitation program, this article employs a quasi-experimental design to evaluate the effectiveness of PBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 76 publications
0
23
0
1
Order By: Relevance
“…There were three quasi-experimental studies (Lu 2014;McBeath and Meezan 2009;Washington et al 2009), two of which looked at the impact of outcome-based contracting on clients, one in child welfare and one in employment. Both found improvement in performance on measures related to payment, but worse performance or no improvement on measures of desirable outcomes not related to payments.…”
Section: Overall Methodological Issuesmentioning
confidence: 99%
See 3 more Smart Citations
“…There were three quasi-experimental studies (Lu 2014;McBeath and Meezan 2009;Washington et al 2009), two of which looked at the impact of outcome-based contracting on clients, one in child welfare and one in employment. Both found improvement in performance on measures related to payment, but worse performance or no improvement on measures of desirable outcomes not related to payments.…”
Section: Overall Methodological Issuesmentioning
confidence: 99%
“…Most outcome-based employment services contracts have tiers of payment, where people who face more difficulty finding and sustaining work attract higher payments (Department of Employment 2015; Lu, 2014). Despite this, several studies found that the incentives to service the most difficult clients were insufficient: these clients had poorer outcomes, were underserved, or 'parked' (Business Council of Australia 2014; Koning and Heinrich 2013;National Audit Office 2015).…”
Section: Employment Servicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Importante destacar que a primeira justificativa para a utilização dos outputs deve-se ao fato de ser o item mais representativo do contrato de gestão, isto é, praticamente todo o desenho e especificação do contrato baseia-se na produção assistencial a ser realizada pelos hospitais gerais. Em segundo lugar, a contratualização baseada em desempenho também pressupõe o foco na produção realizada, ou seja, o contratado é remunerado após a entrega dos serviços pré-estabelecidos no contrato (Lu, 2015 …”
Section: Etapas Da Pesquisaunclassified